1987
DOI: 10.1055/s-2008-1025675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Exercise on Some Parameters of Immunity in Conditioned Sportsmen

Abstract: The studies were performed on 20 conditioned cyclists and 19 untrained men. At rest absolute and percent number of neutrophils, eosinophils, and monocytes, neutrophil bactericidal activity, and blood plasma beta-glucuronidase, acid phosphatase, and lactic dehydrogenase (LDH) activities were similar in sportsmen and untrained men, while neutrophil adherence was lowered in sportsmen. Maximal physical exercise induced significant rises in absolute numbers of neutrophils and monocytes in both groups. In sportsmen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0
7

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 6 publications
8
46
0
7
Order By: Relevance
“…It was reported that helper T cells decrease and suppressor T cells increase immediately after exercise irrespective of its intensity, but both types of T cells return to the pre-exercise level 2 h after discontinuation of exercise. 15 Hashimoto et al evaluated immune responses in rats in a 7-week training group, an acute exercise group, and a control group and found a decrease in lymphocytes in the acute exercise group and enhanced granulocyte phagocytosis in the training group. 16 Reactivity to ConA was reported to decrease after acute exercise irrespective of its intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that helper T cells decrease and suppressor T cells increase immediately after exercise irrespective of its intensity, but both types of T cells return to the pre-exercise level 2 h after discontinuation of exercise. 15 Hashimoto et al evaluated immune responses in rats in a 7-week training group, an acute exercise group, and a control group and found a decrease in lymphocytes in the acute exercise group and enhanced granulocyte phagocytosis in the training group. 16 Reactivity to ConA was reported to decrease after acute exercise irrespective of its intensity.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] In recent years, exercise and training have been studied as factors affecting immune responses. [14][15][16][17][18][19][20] We have performed sports rehabilitation for patients with coronary heart disease from the aspect of exercise psychology. As part of studies on the effects, in particular the preventive effects, of exercise and psychological factors on coronary heart disease, the present study evaluated the association between immune responses and psychological factors.…”
mentioning
confidence: 99%
“…Most reports indicate that neutrophil adherence to the endothelium (which is the first stage in diapedesis) is not affected by acute exercise of a moderate (Ortega et al 1993b) or exhausting nature (Lewicki et al 1987, Rodriguez et al 1991, although Lewicki et al (1987) observed an attenuation of this function during acute exercise in trained individuals. Neutrophil adherence at rest has been reported to be lower (Lewicki et al 1987) or unaltered (Ortega et al 1993a) in trained individuals compared with controls.…”
Section: Neutrophil Chemotaxis and Adherencementioning
confidence: 99%
“…Most reports indicate that neutrophil adherence to the endothelium (which is the first stage in diapedesis) is not affected by acute exercise of a moderate (Ortega et al 1993b) or exhausting nature (Lewicki et al 1987, Rodriguez et al 1991, although Lewicki et al (1987) observed an attenuation of this function during acute exercise in trained individuals. Neutrophil adherence at rest has been reported to be lower (Lewicki et al 1987) or unaltered (Ortega et al 1993a) in trained individuals compared with controls. Neutrophil chemotaxis may be enhanced by acute moderate exercise (Ortega et al 1993b) or unchanged by single bouts of exhaustive exercise (Rodriguez et al 1991), while being higher (Ortega et al 1993a) or no different (Hack et al 1992) in trained versus untrained individuals.…”
Section: Neutrophil Chemotaxis and Adherencementioning
confidence: 99%
See 1 more Smart Citation